ARABIC 1 MAQAMAAT-UL-IMAM JALAL-U-DIN AL-SYUTI: مقامات الامام جلال الدّين السيوطي (رحمة الله عليه) - Nazar, Shabana (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2021)
Al-Imam Al-Syuti is a great Scholar and Interpreter of The Holy Quran. He has written hundreds of books on different Fields of life and Topics. Everyone is acknowledged of his disclosure of Tafseer and his Books of Islamic Literature, Particularly his Book “Al-Muzhir” which held the Primary source of Linguistics. But He is also an excellent writer, scholar and expert of Arabic Language and Literature. His Book of Maqaamat is the evidence of his excellent writing and expertise of Arabic Language, which has been written with fine and eloquent Arabic words. This article is subjected to highlight certain aspects of his Book “Maqamaat-us-Syuti”. This Collection of Maqamaat is the fine example of Arabic Language and narrative styles. These Maqaamat are excellent addition in Arabic Literature. The topic of discussion of these Maqaamat is correction of Society and improvement of human being. This article is designed to introduce the procedure, style, characteristics and way of analysis of his Book of Maqaamat.